Bilateral indirect inguinal herniation of ovaries in a young female with Mayer-Rokitansky-Kuster-Hauser syndrome: An exceptional radiological encounter (Indian Journal of Case Reports, 2026)
We report a rare radiological diagnosis of bilateral indirect inguinal herniation of both ovaries in a 15-year-old girl who presented with primary amenorrhea and normal secondary sexual characteristics. Initial pelvic ultrasonography showed the absence of the uterus in the pelvis and both ovaries within the inguinal canals, each with normal follicular morphology. A preliminary magnetic resonance imaging (MRI) examination performed elsewhere was misinterpreted as aplasia of both the uterus and ovaries. Repeat review at our institution, using dedicated high-resolution pelvic MRIsequences, confirmed Mullerian agenesis consistent with Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome. Both ovaries were located within bilateral inguinal canals, anterior to the urinary bladder, without torsion or infarction. Endocrine evaluation (follicle-stimulating hormone, luteinizing hormone, thyroid-stimulating hormone, prolactin, estradiol, and androgens) was within age-appropriate reference ranges, supporting preserved ovarian function. The patient and guardians were counseled on the risks of torsion and ischemic insult in ectopic ovaries, fertility implications, and the need for timely surgical reduction and fixation. This case highlights a major diagnostic pitfall in MRKH syndrome: Non-visualization of ovaries in the pelvis does not equate to ovarian agenesis. Targeted sonographic and MRI evaluation of the inguinal region is essential to identify ectopic ovaries and guide appropriate counseling and management.